QUALITY OF PATIENT-MEDICAL COMMUNICATION DURING COVID-19 PANDEMIC (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, we have focused on the aspects that are important for the medical staff to pay attention to when talking with the patient. Factors that are simple and not considered important for everyone can also be considered important for the patient who is struggling with the disease. Therefore, it is admirable that despite the complications in the work process (discomforts in protective clothing, talking through a mask in hot weather), the medical staff are focusing on the patient's recovery. However, as with any work process, this system has its flaws and processes that need to be improved. In the article, we analyze these problems and their solutions.